Political donations, public procurement and government efficiency - Vitezslav Titl; Kristof De Witte; Benny Geys (Center for Economic Studies and ifo Institute (CESifo), 2019)
Firms' political donations can induce distortions in the allocation of public procurement contracts. In this article, we employ an advanced non-parametric efficiency model to study the public sector (cost) efficiency implications of such distortions. Using a unique dataset covering the Czech regions over the 2007-2014 period, we find that the efficiency of public good provision is lower when a larger share of public procurement contracts is awarded to firms donating to the party in power (`party donors'). We link this efficiency difference to two underlying mechanisms: i.e. shifts in procurement contract allocations from firms with previous procurement experience to party donors, and the use of less restrictive allocation procedures that benefit party donors.
Keywords: H57; D72; C23; 330; political connections; non-parametric efficiency analysis; benefit-of-the-doubt